Changes in the labor supply behavior of married women: 1980 - 2000 - Francine D. Blau; Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2006)
Using March Current Population Survey (CPS) data, we investigate married women's labor supply behavior from 1980 to 2000. We find that their labor supply function for annual hours shifted sharply to the right in the 1980s, with little shift in the 1990s. In an accounting sense, this is the major reason for the more rapid growth of female labor supply observed in the 1980s, with an additional factor being that husbands' real wages fell slightly in the 1980s but rose in the 1990s. Moreover, a major new development was that, during both decades, there was a dramatic reduction in women's own wage elasticity. And, continuing past trends, women's labor supply also became less responsive to their husbands' wages. Between 1980 and 2000, women's own wage elasticity fell by 50 to 56 percent, while their cross wage elasticity fell by 38 to 47 percent in absolute value. These patterns hold up under virtually all alternative specifications correcting for: selectivity bias in observing wage offers; selection into marriage; income taxes and the earned income tax credit; measurement error in wages and work hours; and omitted variables that affect both wage offers and the propensity to work; as well as when age groups, education groups and mothers of small children are analyzed separately.
Keywords: J16; J22; 330; labor supply; married women; wages; Arbeitsangebot; Frauen; Ehe; USA